Hellenismos: Texts in the Contemporary Worship of the Ancient Greek Gods in North America - Torjussen, Stian Sundell (The pomegranate, 2020)
The article explores worship of ancient Greek gods among three contemporary Pagan groups in North America. The main focus is on how the groups use texts, both ancient and modern, in their theology and rituals. The groups’ approaches are explored through interviews, analyses of websites, and the texts referred to. How do the groups approaches differ from each other and what can we learn from their different reconstruction strategies?